Tunneling nanotubes: A possible highway in the spreading of tau and other prion-like proteins in neurodegenerative diseases. Issue 5 (2nd September 2016) - Abounit, Saida; Wu, Jessica W.; Duff, Karen; Victoria, Guiliana Soraya; Zurzolo, Chiara
ABSTRACT: The mechanisms of intercellular spreading of amyloidogenic proteins involved in neurodegenerative diseases have yet to be fully elucidated. While secretion has been implicated in the transfer of many proteins, including prions and α-synuclein, tunneling nanotubes (TNTs) have also been demonstrated for prions and mutant Huntingtin. Here, we provide further evidence that Tau aggregates, which have been demonstrated to predominantly be transferred via secretion, can also be found in TNTs. Additionally, cells that have taken up Tau have increased TNT formation. Coupled with previous evidence that other amyloidogenic aggregates also induce TNT formation we propose that misfolded protein aggregates can, through a common mechanism, promote the formation of TNTs and thereby their own intercellular transfer, contributing to the propagation of pathology.